Genetic and Environmental Influences on the Aggregation of Beetles - Meyers, Olivia; Marshall, Jeremy (My University, 2018)
The red flour beetle, or Tribolium castaneum (Coleoptera: Tenebrionidae), is a worldwide pest of stored products, particularlyfeed grains (Baldwin and Faluso 2006). It's tiny body and agile legs allow this beetle to get into tiny niches and contaminate large amounts of stored grains. This beetle cannot feed on intact grains, however thrives on high moisture, cracked or hulled grain which can be a problem in facilities where grain is processed (Gerkin et al 2018). This attraction can lead to an offensive odor, mold growth, and can bring out a grey tint in the grain. It is unknown whether the red flour beetle aggregates based on their environmentordue to familiar, genetic pheromones in the air (Johnson). Therefore, the purpose of this research is to place two strains of red flour beetle together and observe theiraggregation preferences. The question is will the beetles solely aggregate with their genetic members, or will they associate with the unfamiliar strain. I believe that the beetles will aggregate in response to genetic cues in their environment. The results of this research are necessary to establishing a better way to manage thisfood storage pest. If the beetles are attracted to genetic pheromones within their environment, then progress can be made to control the pheromone. In turn, this research can help indicate a modified way of controling these beetles.
Keywords: Fall 2018